Malafrena - Le Guin, Ursula K., 1929-2018 (New York : Berkley Books, 1980)
The story is set between 1825 and 1830, during the Austrian Empire's rule over Orsinia. The protagonist, Itale Sorde, is the son of an estate owner near Lake Malafrena, located in the valley of the same name. Defying his father's wishes, Itale departs the estate to pursue nationalist and revolutionary politics in the capital.
Keywords: Malafrena (Imaginary place) -- Fiction; Science fiction